Respuesta :

Step-by-step explanation:

Left hand side:

tan 203° + tan 22° + tan 203° · tan 22°

From angle sum identities, we know:

tan (α + β) = (tan α + tan β) / (1 − tan α · tan β)

Therefore:

tan (203° + 22°) = (tan 203° + tan 22°) / (1 − tan 203° · tan 22°)

tan (225°) = (tan 203° + tan 22°) / (1 − tan 203° · tan 22°)

1 = (tan 203° + tan 22°) / (1 − tan 203° · tan 22°)

tan 203° + tan 22° = 1 − tan 203° · tan 22°

Substituting:

1 − tan 203° · tan 22° + tan 203° · tan 22°

1

ACCESS MORE